(untitled) (Research, Society and Development, 2023)
Objective: to build an assistive technology to prevent the extravasation of chemotherapy drugs. Methods: this is a descriptive, exploratory study, with a qualitative approach, an integrative literature review was used, which allowed us to develop a care protocol for the prevention of extravasation of chemotherapy drugs, containing the behaviors and interventions that nursing should adopt to prevent extravasation, a table was constructed on the classification of chemotherapy drugs according to their potential for dermatological toxicity. Results: from the findings in the RIL, 3 categories emerged, where the main needs for the construction of the protocol were discussed. From this, the protocol was built, which contains information about the team’s conduct and management with antineoplastic drugs, a data collection script that allows the description of extravasation, the classification of chemotherapy according to the potential of dermatological toxicity. Conclusion: the construction of a care technology for the prevention of extravasation of chemotherapy drugs contributes to greater vigilance on the part of professionals, promotes the reduction of damage resulting from these incidences and enables immediate conduct and decision-making, however, it is necessary that the professionals are continually trained to perform this management in an appropriate and safe way for the patient.